Uptake, excretion and toxicity of titanate nanotubes in three stains of free-living ciliates of the genus Tetrahymena - Ren Kong; Qian Sun; Shiyang Cheng; Fu, Jie; Liu, Wen; Robert J. Letcher; Chunsheng Liu (Aquatic Toxicology, 2021)
The potential exposure of titanate nanotubes (TNTs) to wildlife and humans may occur as a result of increased use and application as functional nanomaterials. However, there is a dearth of knowledge regarding the pathways of uptake and excretion of TNTs and their toxicity in cells. In this study, three strains of the Tetrahymena genus of free-living ciliates, including a wild type strain (SB210) and two mutant strains (SB255: mucocyst-deficient; NP1: temperature-sensitive “mouthless’’), were used to study the pathways of uptake and excretion and evaluate the cytotoxicity of TNTs. The three Tetrahymena strains were separately exposed to 0, 0.01, 0.1, 1 or 10 mg/L of TNTs, and cells were collected at different time points for quantification of intracellular TNTs (e.g., 5, 10, 20, 40, 60, 90 and 120 min) and evaluation of cytotoxicity (12 and 24 h). TNT contents in NP1 and SB255 were greater or comparable to the contents in SB210 while exposure to 10 mg/L TNTs in 120 min. Furthermore, exposure to 10 mg/L TNTs for 24 h caused greater decreases in cell density of NP1 (38.2 %) and SB255 (36.8 %) compared with SB210 (26.5 %) and upregulated the expression of caspase 15 in SB210. Taken together, our results suggested that TNT uptake by pinocytosis and excretion by exocytosis in Tetrahymena, and the exposure could cause cytotoxicity which can offer novel insights into the accumulation kinetics of nanotubes and even nanomaterials in single cell.
Keywords: Cytotoxicity; Excretion; Titanate nanotubes; uptake